Lithium adsorption performance of a three-dimensional porous H2TiO3-type lithium ion-sieve in strong alkaline Bayer liquor. Issue 31 (28th March 2017) - Xu, Xin; Zhou, You; Fan, Maohong; Lv, Zijian; Tang, Yang; Sun, Yanzhi; Chen, Yongmei; Wan, Pingyu
Abstract : A three-dimensional porous H2 TiO3 -type lithium ion-sieve prepared by polystyrene colloidal microspheres template was applied to selectively adsorb Li + ions from the strong alkaline Bayer liquor. Abstract : Removing lithium from the Bayer liquor for ensuring good alumina product quality demands a special lithium ion-sieve (LIS) with good stability in a strong alkaline medium. In this study, a three-dimensional porous H2 TiO3 -type LIS (porous-HTO) prepared by a polystyrene (PS) colloidal microspheres template was applied to adsorb Li + from the strong alkaline Bayer liquor. XRD and SEM results confirm the fine stability of porous-HTO in strong alkaline medium, and the regeneration tests show that more than 64 mg g −1 lithium adsorption capacity still remains even after 5 cycles of lithiation–delithiation in the simulation Bayer liquor. The lithium adsorption processes of porous-HTO and bare H2 TiO3 -type LIS (bare-HTO) both fit the pseudo-second-order model, but the adsorption capacity and the adsorption rate of the porous-HTO are much better than those of the bare-HTO. For porous-HTO, the adsorption rate constant is 0.02357 g mg −1 h −1 and the equilibrium adsorption capacity is 76.3 mg g −1, while for bare-HTO, the adsorption rate constant is 0.009682 g mg −1 h −1 and the equilibrium adsorption capacity is only 44.8 mg g −1 . The lithium selectivity tests demonstrate that the coexisting ions including Na +, K +, AlO2 −, SiO3 2− in the simulation Bayer liquor have low influence on lithium adsorption. The simulation Bayer liquors with Li + ions of 56.00, 30.00 and 5.00 mg L −1 are all reduced to below 1.00 mg L −1 by virtue of one-time-adsorption of porous-HTO at various solid to liquid ratios of 1.0, 0.5 and 0.1 g L −1, respectively.